2018
DOI: 10.1088/1367-2630/aaa951
|View full text |Cite
|
Sign up to set email alerts
|

Photodetachment and Doppler laser cooling of anionic molecules

Abstract: We propose to extend laser-cooling techniques, so far only achieved for neutral molecules, to molecular anions. A detailed computational study is performed for C 2 -molecules stored in Penning traps using GPU based Monte Carlo simulations. Two cooling schemes-Doppler laser cooling and photodetachment cooling-are investigated. The sympathetic cooling of antiprotons is studied for the Doppler cooling scheme, where it is shown that cooling of antiprotons to subKelvin temperatures could becomes feasible, with impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…The spectroscopy of the C − 2 anion has been well studied [14][15][16][17]. The ground-state anion is nominally described by the configuration 1σ 2 g 1σ 2 u 2σ 2 g 2σ 2 u 1π 4 u 3σ g , 2 Σ + g .…”
Section: Computational Resultsmentioning
confidence: 99%
“…The spectroscopy of the C − 2 anion has been well studied [14][15][16][17]. The ground-state anion is nominally described by the configuration 1σ 2 g 1σ 2 u 2σ 2 g 2σ 2 u 1π 4 u 3σ g , 2 Σ + g .…”
Section: Computational Resultsmentioning
confidence: 99%
“…8 Additionally, photodetachment cooling has been tried and shown that even lower temperatures could be accessed during the process. 9 For the preparation of the trapped anions into their lowest internal states by collisions with neutrals to be efficient, the system has to exhibit a large ratio of elastic or rotationally inelastic collisions to reactive collisions, since the latter could lead to a loss of the original ions by the opening of possible charge-exchange channels. 10 This last requirement therefore explains the preference for using one of the noble gases as the buffer gas in the cold ion traps.…”
Section: Introductionmentioning
confidence: 99%
“…and B 2 + u electronic states have large Franck-Condon overlap factors with the X 2 + g ground state for transitions between their lowest vibrational levels [25,28]. Simulations of laser cooling using the B 2 + u [1] and A 2 u [29] states suggests that C − 2 can, in principle, be cooled efficiently to milikelvin temperatures using Doppler or Sisyphus cooling in Paul or Penning traps and that photodetachment could access even lower temperatures [30]. If laser cooling of C − 2 anions were to be realised, it would open up the possibility of sympathetically cooling other anions [29] or even antiprotons [30].…”
Section: Introductionmentioning
confidence: 99%